LC-MS PHENOLIC COMPOSITION CHANGES AND ANTIOXIDANT CAPACITIES OF THE SAHARAN TREE ARGANIA SPINOSA LEAVES UNDER SALNITY - KECHEBAR, M. S. A.; KAROUNE, S.; FALLEH, H.; BELHAMRA, M.; RAHMOUNE, C.; KSOURI, R. (Courrier du Savoir, 2017)
Adaptation of many plant species to hostile environmental conditions suggest the presence of powerful antioxidative constituents in their tissues such as phenolic compounds. Many works on antioxidant activity of the Moroccan argan oil have been carried out. However, it is the first time that salt impact on Algerian arganleaves is assessed. The main objective of this work was to study the soil salinity impact on phenolic content and composition, and the antioxidant activities of the argan leaves collected from three point in the same site of Tindouf region (Algeria) characterized by a gradient of salt concentration (Lightly Salt Tindouf, Salt Tindouf and Very Salt Tindouf). Variability of phenolic contents, antioxidant and free radical-scavenging activities of the argan leaves as function of salt soil concentration were evaluated. Identification was done by LC-MS system. Regarding phenolic contents (total polyphenol, flavonoid and condensed tannin), the Salt Tindouf leaves displayed the highest amounts (total polyphenol = 77.28 mg GAE/g DW). Moreover, the same tendency was observed for antioxidant activities, for instance, total antioxidant activity of leaves from Salt Tindouf was the highest (83.6 mg GAE/g DW). In addition, leaves from Salt Tindouf displayed the highest scavenging activity against DPPH radical (IC50 = 6.5 μg/ml) as compared to the two others points. These results were also confirmed by LC-MS analyses. Leaves synthesize more compounds with very important biological activities under salinity which allow them to be valorized in different fields, such as pharmacology and agro-food industries.